EVALUASI KETERSEDIAAN FASILITAS DAN AKSESIBILITAS BAGI PENYANDANG CACAT PADA GEDUNG BPJS KESEHATAN KOTA SEMARANG - Wardani, Fernanda Charisma; Kismartini, Kismartini; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2015)
Facility and accessibility difables are an assurance for life right and living in society. Obligation of the government to provide the facilities and accessibility for people with difables in the building infrastructure has been set in the rules and legislation. Fulfillment facilities and accessibility for people with difables, there are several things to consider, including usability, safety, convenience and independence. The main problem of this research is in BPJS’s office that hasn’t implemented the difables facilities and accessibilitymaximally. So that, it’s needes to be evaluated of implementing the difables facilities and accessibility in BPJS’s office Semarang city, according to Permen PU No. 30/PRT/M/2006 with purpose for knowing how for the implementation of this policy in real sector especially in BPJS’s office Semarang city. This research uses descriptive research methods. The technique of collecting data by in-dept interviews, documentation and observation studies. The result of this research about evaluation availability of difables facility in BPJS’s office Semarang city shows that it has some facilities and it has fulfilled the policy, but in the other hand, in fact there are some facility that haven’t had by this office. Some facilities that they have are door, stairs, washbowl, lift, ramp, toilet and fixtures and control equipment. In addition there factors that lead to a lack of facilities and accessibilityfor people with difables encountered in field, namely lack of understanding Permen PU No. 30/PRT/M/2006 by the BPJS’s Semarang city and BPJS has its own rulesregarding standards development planning facilities are accessible for citizen so not comply with Permen PU No. 30/PRT/M/2006.